Socio-economic Inequalities in the Americas—A Mitigating Educational Approach (Journal of Education and Development, 2018)
A long-range educational approach aiming to mitigate the social and economic inequalities in the Americas is presented. The approach is based on a history book that emphasizes the socio-economic evolution in 28 countries of the American Continent. The book is currently used for courses in pilot schools in Central America and its extension is planned to leading institutions in North America. A phenomenological framework facilitates the identification of novel strategies for the harmonization of different ethnic groups and economic development.